Strategies to prevent missed nursing care: An international qualitative study based upon a positive deviance approach. (3rd November 2020) - Longhini, Jessica; Papastavrou, Evridiki; Efstathiou, Georgios; Andreou, Panayiota; Stemmer, Renate; Ströhm, Christina; Schubert, Maria; de Wolf‐Linder, Susanne; Palese, Alvisa
Abstract: Aim: To identify the strategies to prevent missed nursing care (MNC) that can be implemented by nurse managers/directors on a daily basis. Background: Only few recommendations have been established to date aiming at supporting nurse managers/ directors in preventing MNC. However, several strategies are implemented on a daily basis, suggesting that a body of tacit, practical and wise knowledge is already in place. Method(s): An international qualitative descriptive study based on the positive deviance approach conducted in 2019−2020 and reported according to the Consolidated Criteria for Reporting Qualitative Research. A purposeful sample of 35 nurse managers/directors working in hospitals in Cyprus, Italy, Germany and Switzerland was involved. Codes were extracted from each country, and a thematic analysis was performed at the transnational level to identify strategies and interventions preformed to prevent MNC. Results: Eight strategies and 22 interventions, mainly with preventive intent and designed at the hospital level, affecting both the processes and the structural dimensions, have been reported as effective in preventing MNC. Conclusion: Nurse leaders are involved daily in implementing strategies to minimise MNC at the nursing and at the hospital system levels, integrated with each other. Implications for Nursing Management: Preventing MNC should be a core value of the entire hospital, and not merely a nursing issue. Therefore, complex interventions at the system level are required.